Development of Mobile Learning Application for Diabetic Nutrition using Augmented Reality - FAUZI, NUR AFIQAH; SUPARJOH, SURIAWATI (Applied Information Technology And Computer Science, 2025)
Diabetes has been suffering due to unbalanced food intake as the main cause. The increasing significance of nutritious foods necessitates the imparting of nutrition knowledge to diabetic patients. The existing application very commonly lacks the essence of an interesting application, and lack of having a specific guide on the nutritional content of fruits for diabetic patients. Thus, in this project, an application based on augmented reality has been proposed to share knowledge about nutritional intake for diabetic patients based on the contents of Malaysian health care called Diabetic Nutrition AR (Fruits). This application uses the "Multimedia Mobile Content Development (MMCD)" approach as the methodology of this project. Furthermore, this application aims to guide diabetic patients in explaining information about fruit nutrition using AR technology.